Hydraulic Performance and Mitigation of Biofouling in Drippers Applying Aquaculture Effluent with Anti-Clogging Fertilizer - Layla Bruna Lopes Reges; Rafael Oliveira Batista; Lidianne Leal Rocha; Gustavo Lopes Muniz; Laio Ariel Leite de Paiva; Francisco Éder Rodrigues de Oliveira; José Francismar de Medeiros; Antônio Gustavo de Luna Souto; Luiz Fernando de Sousa Antunes; Eulene Francisco da Silva; Norlan Leonel Ramos Cruz; Luara Patrícia Lopes Morais (AgriEngineering)
Water scarcity in Brazil’s semi-arid region necessitates the agricultural reuse of aquaculture effluents, although emitter clogging remains a challenge. This study evaluated clogging mitigation in drip irrigation systems using liquid anti-clogging fertilizer. The experiment employed a split–split–plot scheme with three water treatments (supply water, aquaculture effluent, and effluent with liquid fertilizer) and three emitter types (ST, SL, and GA), assessing performance over 360 h. A water quality analysis at 0, 160, and 360 h complemented hydraulic evaluations of the average flow rate variation and Christiansen uniformity coefficient measured every 40 h. Energy-dispersive X-ray spectroscopy, X-ray diffractometry, and scanning electron microscopy were used to characterize biofouling. The results showed that the liquid fertilizer mitigated the clogging by biofouling in the three types of emitters, but only the ST emitter presented acceptable hydraulic performance rates. There are relationships between the anti-clogging effect of the liquid fertilizer, the structural characteristics of the emitters, and the flow velocity inside the labyrinths. The SL dripper applying only aquaculture effluent presented the highest clogging rate due to biofouling. Agricultural reuse is a strategy for the rational use of water resources that is of great relevance for arid and semi-arid regions and can insert aquaculture into the circular economy.